The Effect of Profitability, Independent Commissioner, Audit Committee, and Managerial Ownership on Disclosure of Islamic Corporate Social Responsibility - Surepno, Surepno; Ermia Wirdamita, Zunaefa (LPPM Universitas Terbuka, 2022)
This study aims to determine the effect of profitability, independent commissioners, audit committees, and managerial ownership on the disclosure of Islamic Corporate Social Responsibility in health sector companies. This type of research is a quantitative study with a population of health sector companies listed on the Indonesian Sharia Stick Index (ISSI) in 2018-2020. Determination of the sample in this study using purposive sampling method with pretermined criteria, in order to obtain 13 of 23 companies in the health sector. The research period was 5 years, so that 39 samples were obtained. The analytical methods used include descriptive statistics, classical assumption test, multiple linear regression analysis test, and hypothesis test. The results show that simultaneously the variables of profitability, independent commissioners, audit committees, and managerial ownership have an effect on the disclosure of Islamic Corporate Social Responsibility. While partially, the independent commissioner variable has an effect on the disclosure of Islamic Corporate Social Responsibility in health sector companies listed. The variables of profitability, audit committees, and managerial ownership have no effect on the disclosure of Islamic Corporate Social Responsibility in health sector companies listed on the Indonesian Sharia Stock Index (ISSI) in 2018-2020.